2010
DOI: 10.1128/jvi.00447-10
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Human Respiratory Syncytial Virus Infectivity by Antibodies and Low-Molecular-Weight Compounds Targeted against the Fusion Glycoprotein

Abstract: Human respiratory syncytial virus (HRSV) fusion (F) protein is an essential component of the virus envelope that mediates fusion of the viral and cell membranes, and, therefore, it is an attractive target for drug and vaccine development. Our aim was to analyze the neutralizing mechanism of anti-F antibodies in comparison with other low-molecular-weight compounds targeted against the F molecule. It was found that neutralization by anti-F antibodies is related to epitope specificity. Thus, neutralizing and nonn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 78 publications
2
41
0
Order By: Relevance
“…We have demonstrated that 101F does not block virus attachment over a wide range of concentrations (Fig. 5B), which agrees with recently published data showing a similar result at a single antibody concentration (29). We have also shown that 101F is capable of preventing infection once the virus has attached to the cell (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…We have demonstrated that 101F does not block virus attachment over a wide range of concentrations (Fig. 5B), which agrees with recently published data showing a similar result at a single antibody concentration (29). We have also shown that 101F is capable of preventing infection once the virus has attached to the cell (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Though we demonstrate binding to the postfusion state, these antibodies must neutralize prior to membrane fusion and formation of the six-helix bundle, and therefore, we infer that they can bind intermediate states that at least partially resemble the postfusion conformation. Recently, Magro et al showed that 101F and an antibody specific for antigenic site II bound virus before incubation with target cells, remained bound during ultracentrifugation, and neutralized the virus (26). This result is consistent with 101F and motavizumab being able to bind the prefusion conformation, as well.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, 101F and motavizumab can likely bind the fusion glycoprotein in the prefusion, postfusion, and intermediate states, which results from their epitopes residing in domains that are not expected to undergo large structural rearrangements during the fusion process (44). This is different from the modes of action of other RSVneutralizing compounds, such as antigenic site I-directed antibodies, which appear not to bind the prefusion state (26), and some small molecules and heptad repeat B-derived peptides that target various intermediate states of the F glycoprotein (24,35) (Fig. 7).…”
Section: Discussionmentioning
confidence: 83%
“…Palivizumab is licensed and widely used throughout the world to suppress severe RSV infection in high -risk children 24) . Site IV is recognized by mAb 19 25) or 101 F 26) with moderate NT activity. A recently isolated human mAb, 54G10, shows NT activity for human metapneumovirus (hMPV), which belongs to genus paramyxovirus as RSV 27) .…”
Section: Neutralizing Epitopementioning
confidence: 99%